Association between dietary glycemic index and non-alcoholic fatty liver disease in patients with type 2 diabetes mellitus - Salavatizadeh, Marieh; Soltanieh, Samira; Ataei Kachouei, Amirhossein; Abdollahi Fallahi, Zahra; Kord-Varkaneh, Hamed; Poustchi, Hossein; Mansour, Asieh; Khamseh, Mohammad E.; Alaei-Shahmiri, Fariba; Santos, Heitor O.; Hekmatdoost, Azita (Frontiers in Endocrinology, 2023)
Objective: Managing dietary glycemic index (GI) deserves further attention in the interplay between non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM).This study aimed to evaluate the relationship between dietary GI and the odds of NAFLD in patients with T2DM.A cross-sectional study was carried out between April 2021 and February 2022, including 200 participants with T2DM aged 18-70 years, of which 133 had NAFLD and 67 were in the non-NAFLD groupcontrol group. Cardiometabolic parameters were analyzed using standard biochemical kits and dietary intake was assessed using a validated food frequency questionnaire. Binary logistic regression was applied to explore odds ratios (ORs) and 95% confidence intervals (CIis) for NAFLD according to tertiles of dietary GI.Results: Highest vs. lowest tertile (< 57 vs. > 60.89) of energy-adjusted GI was not associated with the odds of having NAFLD (OR 1.25, 95% CI = 0.6-2.57; P-trend = 0.54) in the crude model. However, there was an OR of 3.24 (95% CI = 1.03-10.15) accompanied by a significant trend (P-trend = 0.04) after full control for potential confounders (age, gender, smoking status, duration of diabetes, physical activity, waist circumference, HbA1c, triglycerides, total cholesterol, dietary intake of total carbohydrates, simple carbohydrates, fat, and protein).High dietary GI is associated with increased odds of NAFLD in subjects with T2DM. However, interventional and longitudinal cohort studies are required to confirm these findings.